2020
DOI: 10.3390/brainsci10100730
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neural Changes after Low-Frequency Bilateral Globus Pallidus Internus Deep Brain Stimulation for Post-Hypoxic Cortical Myoclonus: Voxel-Based Subtraction Analysis of Serial Positron Emission

Abstract: Post-hypoxic myoclonus (PHM) and Lance–Adams syndrome (LAS) are rare conditions following cardiopulmonary resuscitation. The aim of this study was to identify functional activity in the cerebral cortex after a hypoxic event and to investigate alterations that could be modulated by deep brain stimulation (DBS). A voxel-based subtraction analysis of serial positron emission tomography (PET) scans was performed in a 34-year-old woman with chronic medically refractory PHM that improved with bilateral globus pallid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Ramdhani et al 8 were the first to review DBStreated LAS, and they stimulated bilateral GPi in an LAS patient with a CPA etiology and an interval of three years between the injury and DBS. In their 5 reported a case involving low frequency (110 Hz) GPi-DBS, with an interval of three years from injury to DBS. They also published a successful clinical result, with a 35% improvement in action myoclonus at the 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramdhani et al 8 were the first to review DBStreated LAS, and they stimulated bilateral GPi in an LAS patient with a CPA etiology and an interval of three years between the injury and DBS. In their 5 reported a case involving low frequency (110 Hz) GPi-DBS, with an interval of three years from injury to DBS. They also published a successful clinical result, with a 35% improvement in action myoclonus at the 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we present an LAS case that did not benefit from bilateral GPi-DBS, unlike the five cases published in the literature. [4][5][6][7][8]…”
Section: Introductionmentioning
confidence: 99%
“…There was a large body evidence that described deep brain stimulation of PPN either alone or combined with STN for improvement in postural stability and axial symptoms in movement disorders. 9 In addition, recently published deep brain stimulation studies in the cases of intractable PHM showed that a mid-range (40 Hz) 10 or 110-Hz frequency 11 stimulation of GPi elicited long-term improvement in both rest and action myoclonus. When the authors observed brain metabolic changes in the former case study using fluorodeoxyglucose positron emission tomography, increased metabolism was found in thalamus, pontine tegmentum, and medulla, 10 that is, in line with the previous functional imaging study.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, recently published deep brain stimulation studies in the cases of intractable PHM showed that a mid-range (40 Hz) 10 or 110-Hz frequency 11 stimulation of GPi elicited long-term improvement in both rest and action myoclonus. When the authors observed brain metabolic changes in the former case study using fluorodeoxyglucose positron emission tomography, increased metabolism was found in thalamus, pontine tegmentum, and medulla, 10 that is, in line with the previous functional imaging study. 3 In addition, the red nucleus is believed to supplement the dominant corticospinal tract in controlling trunk and limb movements.…”
Section: Discussionmentioning
confidence: 99%
“…Among the myoclonic disorders, MD is the most common myoclonus disorder responsive to pallidal stimulation [ 4 ], in keeping with the observation that pallidal neuronal firing is modulated by the occurrence of myoclonus [ 4 ]. While the myoclonus in MD is subcortical, the myoclonus in CD is of cortical origin [ 5 , 7 ]. Based on the different responses to GPi DBS, pallidal stimulation could be effective mainly for subcortical myoclonus, although its effect on cortical myoclonus is still unclear.…”
mentioning
confidence: 99%